ANALISIS DISPARITAS WILAYAH DI PROVINSI ACEH: TELAAH PADA DANA OTONOMI KHUSUS - Devi Andriyani; Hijri Juliansyah (LPPM UNIMAL, 2018)
The Special Autonomy (OTSUS) allocation policy for the Aceh Province is a source of revenue that is able to increase regional fiscal degrees. Based on Qanun (Perda) No. 10 of the new 2016 passed as amendments to Qanun No. 2 of 2008, the procedure for allocating and distributing OTSUS funds is given full authority to the Province. The concern that arises is that regional expenditure programs funded by OTSUS funds can create disparities in development between districts / cities. This study wants to identify the model of regional disparity in Aceh in terms of the OTSUS Aceh fund allocation policy. Specific research aims to determine the OTSUS fund allocation policy model that avoids disparity between districts / cities. The analysis model uses the formulation of theil index region disparity index which is then carried out multiple linear regression estimation panel data estimation. The results of the study indicate that the disparity in Aceh Province during the OTSUS period has decreased. Disparity is absorbed predominantly in the intra-region (within region) group in the South West, Middle East, and North East. The allocation of OTSUS funds has a significant impact in reducing regional disparity, both in time series and panel analysis. The results of the study concluded that the gap that occurred in Aceh Province was due to the weak factor in providing basic needs, such as education and health. Therefore, the management of OTSUS funds must be carried out precisely in improving aspects of education and health services in Aceh Province.